Do hyperoxaemia and hypocapnia add to the risk of brain injury after intrapartum asphyxia?. Issue 1 (21st December 2004) - Klinger, G; Beyene, J; Shah, P; Perlman, M
Abstract : Background: Episodes of hyperoxaemia and hypocapnia, which may contribute to brain injury, occur unintentionally in severely asphyxiated neonates in the first postnatal hours. Objective: To determine whether hyperoxaemia and/or hypocapnia during the first 2 hours of life add to the risk of brain injury after intrapartum asphyxia. Methods: Retrospective cohort study in term infants with post-asphyxial hypoxic ischaemic encephalopathy (HIE) born between 1985 and 1995. Severe and moderate hyperoxaemia were defined as Pao 2 >26.6 and Pao 2 >13.3 kPa (200 and 100 mm Hg). Severe and moderate hypocapnia were defined as Paco 2 <2.6 and Paco 2 <3.3 kPa (20 and 25 mm Hg). Adverse outcome ascertained by age 24 months was defined as death, severe cerebral palsy, or any cerebral palsy with blindness, deafness, or developmental delay. With outcome as the dependent variable, multivariate analyses were performed including hyperoxaemic and hypocapnic variables, and factors adjusted for initial disease severity. Results: Of 244 infants, 218 had known outcomes, 127 of which were adverse (64 deaths, 63 neurodevelopmental deficits). Multivariate analyses showed an association between adverse outcome and episodes of severe hyperoxaemia (odds ratio (OR) 3.85, 95% confidence interval (CI) 1.67 to 8.88, p  =  0.002), and severe hypocapnia (OR 2.34, 95% CI 1.02 to 5.37, p  =  0.044). The risk of adverse outcome was highest in infants who had both severe hyperoxaemia and severe hypocapnia (OR 4.56, 95% CI 1.4 to 14.9, p  =  0.012). Conclusions: Severe hyperoxaemia and severe hypocapnia were associated with adverse outcome in infants with post-asphyxial HIE. During the first hours of life, oxygen supplementation and ventilation should be rigorously controlled.